Characterisation of low-frequency sea level oscillations in the Mediterranean sea - Bertoncelj, Vesna (Acta hydrotechnica, 2019)
Implementing adequate defences for low-lying coastal area against coastal flooding requires thorough knowledge of all potential influences leading to increased sea levels, including low-frequency sea level oscillations. We present and describe several methods applicable for the analysis of low-frequency sea level oscillations in the Mediterranean Sea: wavelet analysis, spectral analysis, moving-periodogram analysis, and rotary spectral analysis. These methods were applied for characterisation of subinertial sea level oscillations with periods greater of the period of inertial oscillation (18 hours in the Northern Adriatic Sea) on measured sea surface elevations and current velocities in the Mediterranean Sea. Preliminary analysis was performed on observations of a storm event in the Adriatic Sea at the end of January and the beginning of February 2014, revealing a peak in the frequency spectrum in the frequency band between 0.3-0.4 day -1. Further analysis was done on long-term tide gauge measurements available for 62 stations in the Mediterranean basin. The application of the selected methods provided a preliminary set of seasonal occurrences and durations of subinertial oscillation. This sets the ground for further investigation into the propagation of low-frequency sea level oscillations throughout the Mediterranean basin and for characterisation of the mechanisms triggering the process, including with regard to climate change.
Keywords: Adriatic Sea; drseči periodogram; Jadransko morje; Mediterranean Sea; moving periodogram; nihanje morske gladine; sea level oscillations; spectral analysis; spektralna analiza; Sredozemsko morje; subinercialno nihanje; subinertial oscillations; valčna analiza; wavelet analysis